Reseña de Hervás y Panduro, L. (2008). Escuela española de sordomudos - Salazar García, Ventura (Pragmalingüística, 2008)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Hervás y Panduro, L. (2008). Escuela española de sordomudos.